2020
DOI: 10.3390/brainsci10110762
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoresistant Epilepsy in Childhood: Think of the Cerebral Folate Deficiency, a Treatable Disease

Abstract: Cerebral folate deficiency (CFD) is a neurological disorder characterized by low levels of 5-methyltetrahydrofolate (5-MTHF) in the cerebrospinal fluid (CSF). The prevalence of this autosomal recessive disorder is estimated to be <1/1,000,000. Fifteen different pathogenic variants in the folate receptor 1 gene (FOLR1) encoding the receptor of folate α (FRα) have already been described. We present a new pathogenic variation in the FOLR1 in a childhood-stage patient. We aim to establish the core structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Delayed myelination with or without cerebellar atrophy was seen in four patients [ 2 , 13 ]. Apart from the two patients described in this study, infratentorial hypomyelination was described only in one patient [ 23 ], while thinning of the corpus callosum was reported in one other [ 2 ]. MRS values before treatment showed low white matter choline and/or inositol in all patients except for five, which were normal [ 2 , 15 , 19 ].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Delayed myelination with or without cerebellar atrophy was seen in four patients [ 2 , 13 ]. Apart from the two patients described in this study, infratentorial hypomyelination was described only in one patient [ 23 ], while thinning of the corpus callosum was reported in one other [ 2 ]. MRS values before treatment showed low white matter choline and/or inositol in all patients except for five, which were normal [ 2 , 15 , 19 ].…”
Section: Resultsmentioning
confidence: 91%
“…Cerebellar atrophy was absent in seven patients [ 12 , 13 , 15 , 16 , 22 ]. Four patients also had basal ganglia calcifications [ 9 , 16 , 21 , 23 ], one patient had accompanied bilateral temporal cortical laminar necrosis and ulegyria [ 10 ], while one other patient had white matter encephalomalacia [ 17 ]. Two patients had no myelin abnormalities but cerebellar atrophy with or without cerebral calcifications [ 2 , 9 ], and one had cerebral cortical atrophy only [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the affinity of FOLR1 for FA is 14‐fold higher than for 5mTHF 33 . It has also been shown that FOLR1 represents the highest‐affinity folate transport system compared to RFC and PCFT, 34 and also has a higher affinity to FA at neutral pH compared with other folate transporters 35 . Based on this evidence, we speculated that FA could be more readily transported into cells compared with 5mTHF at the same supplemented concentrations due to its higher affinity to FOLR1.…”
Section: Discussionmentioning
confidence: 99%
“…FOLR1 mutations are a rare cause of CFD, and most patients with these mutations share similar clinical phenotypes as those with other common causes, such as frequent epileptic seizures [ 90 , 91 , 92 ]. Mafi et al [ 93 ] attributed the observed myoclonic seizures to the novel variant (c.197 G>A) in FOLR1 identified by WES ( Table 1 ).…”
Section: Application Of Next-generation Sequencing In Neurogenetic Diseasesmentioning
confidence: 99%